The use of Structural Funds and European Investments (ESI) in order to develop the Member States. Examples of good practice in the use of ESI funds - Gabriela Bologa; Casian Butaci (Agora International Journal of Economical Sciences (AIJES), 2016)
Multiannual financial framework of the European Union (EU) for the period 2014-2020 enables implementation of the new generation of EU spending programs since 1 January 2014. EU Member States provide, through the Structural Funds and European Investment Funds or ESI, financial resources to support them in order to develop continuously. This paper discusses disclosure of such funds and a number of issues that need to be known by potential beneficiaries in the Member States.
Keywords: 330